THE INFLUENCE OF FINANCIAL LITERACY, LIFESTYLE, AND INCOME ON CONSUMER ATTITUDES THROUGH FINANCIAL MANAGEMENT AMONG LAW FACULTY STUDENTS AT WIJAYA KUSUMA UNIVERSITY SURABAYA - Kendra Dimapuspa Maharani; Eva Wany (International Journal of Accounting Innovation, 2026)
Objective: This research aims to examine "The Influence of Financial Literacy, Lifestyle, and Income on Consumer Attitude Through Financial Management as a Moderating Variable Among Students of the Faculty of Law, Wijaya Kusuma University Surabaya." Method: This study employs a quantitative method with primary data collected through the distribution of questionnaires to active students of the Bachelor of Law program at Wijaya Kusuma University Surabaya. The research sample consisted of 156 respondents using the purposive sampling method. Data analysis was conducted using Structural Equation Modelling – Partial Least Squares (SEM-PLS) through the SmartPLS application. Results: The results of this study indicate that financial literacy has a positive but not significant effect on consumer attitudes. Lifestyle has a positive and significant effect on consumer attitudes. Income also has a positive and significant effect on consumer attitudes. Financial management is unable to moderate the relationship between financial literacy, lifestyle, and income on consumer attitudes. Novelty: This study examines financial management as a moderating variable in the relationship between financial literacy, lifestyle, income, and consumer attitudes among students of the Faculty of Law, Wijaya Kusuma University Surabaya.